Imperfect information about consumer rights - Baumann, Florian,Friehe, Tim,Wenzel, Tobias (ZEW, 2021)
This paper shows that the provision of consumer rights can decrease welfare when some consumers remain ignorant of these rights. We find that consumers uninformed about a mandated warranty demand excessively safe products in some circumstances. In other circumstances, uninformed consumers buy the efficient product variety like informed consumers but the former cross-subsidize the latter via firms’ pricing. With respect to the salient policy option of improving information about consumer rights, we find that increasing the share of informed consumers may actually raise the risk of inefficiency.
Keywords: Graue Literatur; consumer policy; imperfect information; efficiency; product safety; distribution